A Multi-Step Chromatographic Approach to Purify Radically Generated Ferulate Oligomers Reveals Naturally Occurring 5-5/8-8(Cyclic)-, 8-8(Noncyclic)/8-O-4-, and 5-5/8-8(Noncyclic)-Coupled Dehydrotriferulic Acids - Waterstraat, Martin; Bunzel, Mirko (Frontiers in Chemistry, 2018)
Ferulate-mediated cross-linking of plant cell wall polymers has various implications on the quality of plant based food products, forage digestibility, and biomass utilization. Besides dehydrodiferulic acids (DFA), dehydrotriferulic acids (TriFA) gained increasing interest over the past two decades, because they potentially cross-link up to three polymers. Here, we describe a separation strategy to obtain several TriFA as analytical standard compounds from a reaction mixture after radical coupling of ethyl ferulate. By using silica flash chromatography, Sephadex LH 20 chromatography, and reversed phase HPLC, six known TriFA as well as three previously unidentified ferulic acid trimers were obtained, and their structures were characterized by mass spectrometry and NMR spectroscopy (1H, HSQC, COSY, HMBC, and NOESY). The novel trimers were identified as 5-5/8-8(cyclic)-, 8 8(noncyclic)/8-O-4-, and, tentatively, 5-5/8-8(noncyclic)-TriFA. Natural occurrence of these TriFA in plant cell walls was demonstrated by LC-MS/MS analyses of alkaline cell wall hydrolyzates.